APLIKASI COX PROPORTIONAL HAZARD PADA SINTASAN PASIEN ASMA - PUSPITA, NI NENGAH RIKA; SUSILAWATI, MADE; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 11 No 1 (2022), 2022)
Asthma is defined as a chronic inflammatory disease of the respiratory tract. Since 2013, Bali ranks sixth out of thirty three provinces in Indonesia for the most asthma patient. This study has a purpose to examine the influential factors on the cure rate of asthma patients and determine the best model using the stepwise method. To determine the survival rate of asthma patients, a statistical method that involves censored data is used by applying the Cox Proportional Hazard regression.  The data used in this study were medical records of asthma patients who were hospitalized at the Wongaya Regional General Hospital in Denpasar for the period January , 2019 to April , 2020. The analysis of this study discovered that significant variables for the survival of asthma patients were age and disease.